Seasonal Variation of Aeromycoflora over Ocimum sanctum Plant with Special Reference to Winter Season - Sharma, K. (Journal of Phytology, 2010)
Aeromycoflora over Ocimum sanctum was studied with the help of Rotorod sampler. Total 17315 fungal spores represented 43 fungal types were observed during the present investigation period. Environmental factor play an important role for the distribution of the fungal spores. Out of 43 fungal types, Maximum numbers of fungi (33) were isolated during winter, moderate (28) during rainy and minimum (18) during summer season. In winter season 5300 fungal spores were recorded. Highest 1870 fungal spores were recorded in the month of November,1430 fungal spores were recorded in the month of December, 905 fungal spores during the January and 1095 fungal spores were recorded during the February month. The maximum number of spores of Cladosporium was recorded. On the contrary minimum number of Belterniella spores was observed. Key words: Alternaria, Ocimum sanctum, Rotorod, fungal spores <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">K. Sharma. Seasonal Variation of Aeromycoflora over Ocimum sanctum Plant with Special Reference to Winter Season. J Phytol 2/8 (2010) 01-05.